Answer:
![\boxed {\boxed {\sf B. \ \frac{8}{13} }}](https://tex.z-dn.net/?f=%5Cboxed%20%7B%5Cboxed%20%7B%5Csf%20B.%20%5C%20%5Cfrac%7B8%7D%7B13%7D%20%7D%7D)
Step-by-step explanation:
Probability is found by dividing the number of favorable outcomes by the total number of outcomes.
![P= \frac{favorable \ outcomes}{total \ outcomes}](https://tex.z-dn.net/?f=P%3D%20%5Cfrac%7Bfavorable%20%5C%20outcomes%7D%7Btotal%20%5C%20outcomes%7D)
For this problem, the favorable outcome is selecting a blue or green marble. There are 8 outcomes for this because there are 6 outcomes for blue and 2 fr green.
The total outcomes are all the marbles. Each marble could be an outcome, so there are 13 outcomes (1 for each marble).
![P(blue \ or \ green) = \frac{8}{13}](https://tex.z-dn.net/?f=P%28blue%20%5C%20or%20%5C%20green%29%20%3D%20%5Cfrac%7B8%7D%7B13%7D)
This fraction cannot be reduced, so the probability of selecting a blue or green marble is <u>8/13.</u>
Answer:
Yes, we can assume that the percent of female athletes graduating from the University of Colorado is less than 67%.
Step-by-step explanation:
We need to find p-value first:
z statistic = (p⁻ - p0) / √[p0 x (1 - p0) / n]
p⁻ = X / n = 21 / 38 = 0.5526316
the alternate hypothesis states that p-value must be under the normal curve, i.e. the percent of female athletes graduating remains at 67%
H1: p < 0.67
z = (0.5526316 - 0.67) / √[0.67 x (1 - 0.67) / 38] = -0.1173684 / 0.076278575
z = -1.538681
using a p-value calculator for z = -1.538681, confidence level of 5%
p-value = .062024, not significant
Since p-value is not significant, we must reject the alternate hypothesis and retain the null hypothesis.
Answer:
m∠C = 66°
Step-by-step explanation:
Given
m∠ A = 33°
m∠ B = 81°
To determine
m∠C = ?
We know that sum of angles of a triangle is 180°.
so using the equation
m∠ A + m∠ B + m∠C = 180°
substituting m∠ A = 33°, and m∠ B = 81° in the equatio
33° + 81°+m∠C= 180°
114° + m∠C = 180°
m∠C = 180° - 114°
m∠C = 66°
Therefore,
Hey there! :)
Answer:
![g^{-1} (g(10))=10](https://tex.z-dn.net/?f=g%5E%7B-1%7D%20%28g%2810%29%29%3D10)
Step-by-step explanation:
Begin by calculating g(10):
g(x) = 3x - 6
Substitute in 10 for x:
g(10) = 3(10) - 6
g(10) = 30-6
g(10) = 24.
Plug '24' into 'x' into ![g^{-1} (x)](https://tex.z-dn.net/?f=g%5E%7B-1%7D%20%28x%29)
![g^{-1} (24)=\frac{(24) + 6}{3}](https://tex.z-dn.net/?f=g%5E%7B-1%7D%20%2824%29%3D%5Cfrac%7B%2824%29%20%2B%206%7D%7B3%7D)
Simplify:
![g^{-1} (24)=\frac{30}{3}](https://tex.z-dn.net/?f=g%5E%7B-1%7D%20%2824%29%3D%5Cfrac%7B30%7D%7B3%7D)
![g^{-1} (24)=10](https://tex.z-dn.net/?f=g%5E%7B-1%7D%20%2824%29%3D10)
Answer: 4/5
Step-by-step explanation:
1. you need to know the formula which is m = y2-y1/x2-x1
2. you plug in the numbers which would be 9-5/3-(-2)
3. you get your answer as 4/5
4. the answer is 4/5